Investigation of Ship and Platform Accidents Due to Severe Weather Events by Satellite Radar Data - Results of the MAXWAVE Project - Lehner, Susanne; Rosenthal, Wolfgang (Volume 3: Safety and Reliability; Materials Technology; Douglas Faulkner Symposium on Reliability and Ultimate Strength of Marine Structures, 2006)
Heavy sea states and severe weather conditions have caused the loss of more than 200 super carriers within the last 20 years. In many cases single ‘rogue waves’ of abnormal height as well as groups of extreme waves have been reported by crew members of such vessels. The European Project MAXWAVE dealt with both theoretical aspects of extreme waves as well as new techniques to observe these waves using different remote sensing techniques. The final goal was to improve the understanding of the physical processes responsible for the generation of extreme waves and to identify geophysical conditions in which such waves are most likely to occur. This paper gives a summary of the results of the MAXWAVE projects with emphasis on the analysis of the marine and satellite radar data sets. Two dimensional sea surface elevation fields are derived from marine radar data and complex Spaceborne Synthetic Aperture Radar (SAR) images. Several ship and offshore platform accidents are analysed and new warning criteria are discussed.